Fluoride anion binding by cyclic boronic esters: influence of backbone chelate on receptor integrity. - Bresner, C; Day, J; Coombs, N; Fallis, I; Aldridge, S; Coles, S; Hursthouse, M (2006)
A systematic investigation of fluoride anion binding properties as a function of chelate backbone has been carried out for ferrocene functionalised boronic esters of the types FcB(OR)2 and fc[B(OR)2]2 [Fc = ferrocenyl = (eta5-C5H5)Fe(eta5-C5H4); fc = ferrocendiyl = Fe(eta5-C5H4)2]. Cyclic boronic esters containing a saturated five- or six-membered chelate ring are readily synthesized from ferrocene, and selectively bind fluoride via Lewis acid/base chemistry in chloroform solution. The resulting complexes are characterized by relatively weak fluoride binding (e.g.K = 35.8 +/- 9.8 M(-1) for FcBO2C2H2Ph2-S,S), and by cathodic shifts in the ferrocene oxidation potential that form the basis for electrochemical or colorimetric fluoride detection. The fluoride selectivity of these systems is attributed to relatively weak Lewis acidity, resulting in weak F- binding, and essentially no binding of potentially competitive anions. By contrast, more elaborate Lewis acid frameworks based on calix[4]arene (calixH4), such as (FcB)2calix or fcB2calix, do not survive intact exposure to standard fluoride sources (e.g. [nBu4N]F.xH2O solutions in chloroform or acetonitrile). Instead B-O bond cleavage occurs yielding the parent calixarene; the differences between alkoxo- and aryloxo-functionalised derivatives can be rationalised, at least in part, by consideration of the differences in electron donating capabilities of RO- (R = alkyl, aryl).